Effective Occupation in Territorial Claims: A Legal Analysis and Critique - Setiyawan, Anang; Pangestu, Ilham Aji (Jurnal Pembaharuan Hukum, 2025)
The principle of effective occupation is often used to justify territorial claims based on physical and administrative control; in practice, the application of this principle tends to conflict with fundamental norms in international law such as self-determination and the prohibition of colonization. This article examines the practice and principle of effective occupation that is often used to legitimize territorial claims. This article use normative research with a prescriptive legal approach by analyzing international treaties, international customary law, principles of international law, court decisions, and expert opinions. The Namibia Advisory Opinion and the Western Sahara case illustrates how the principle of effective occupation has marginalized the sovereignty and fundamental rights of indigenous populations. These actions violate peremptory norms, which safeguard human dignity and uphold non-derogable principles such as the prohibition of unlawful occupation and the self-governance of communities. The study’s findings highlight the urgent necessity for a robust legal framework governing territorial claims to ensure they respect fundamental rights and adhere to the foundational principles of international law. This would help prevent the misuse of effective occupation as a justification for territorial expansion while protecting the rights of vulnerable communities.